2016
DOI: 10.1002/2016jd024856
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation δ18O over the Himalaya‐Tibet orogen from ECHAM5‐wiso simulations: Statistical analysis of temperature, topography and precipitation

Abstract: Variations in oxygen isotope compositions (δ18O) provide insight into modern climate and past changes in climate and topography. In addition, in regions such as Tibet, geologic archives of isotope ratios record climate change driven by plateau uplift and therefore also provide information about the surface uplift history. A good understanding of modern‐day controls on δ18O is crucial for interpreting geologic δ18O in this context. We use the ECHAM5‐wiso global atmospheric general circulation model to calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…[] using the same resolution ECHAM5‐wiso model outputs as this study. Thus, the model resolution used in this study agrees with reanalysis data and the different reanalysis data sets agree with each other [ Mutz et al ., ]. Furthermore, our study uses a T63 resolution ECHAM5 model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[] using the same resolution ECHAM5‐wiso model outputs as this study. Thus, the model resolution used in this study agrees with reanalysis data and the different reanalysis data sets agree with each other [ Mutz et al ., ]. Furthermore, our study uses a T63 resolution ECHAM5 model.…”
Section: Resultsmentioning
confidence: 99%
“…This information is important for paleoclimatology and paleoaltimetry studies when interpolating proxy data for the Tibetan Plateau. This SE to the NW direction of δ 18 O p zones and the climate controls on it have been independent of this study identified by a cluster analysis of δ 18 O p [ Mutz et al ., ]. The standard deviation ( σ ) in δ 18 O p was calculated from 90 monthly means of predicted δ 18 O p (30 simulation years × 3 month in a season).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, u-wind and v-wind speeds during (January) and outside (July) the monsoon season in South America are added to the list of considered variables to take into account the South American Monsoon System (SASM) in the cluster analysis for this region. The long-term monthly means of those variables are used in a hierarchical clustering method, followed by a non-hierarchical k-means correction with randomised regroupment (Mutz et al, 2016;Wilks, 2011;Paeth, 2004;Bahrenberg et al, 1992). The hierarchical part of the clustering procedure starts with as many clusters as there are elements (ni), then iteratively combines the most similar clusters to form a new cluster using centroids for the linkage procedure for clusters containing multiple elements.…”
Section: Cluster Analysis To Document Temporal and Spatial Changes Inmentioning
confidence: 99%
“…Despite consistent forcings, experiments carried out with different GCMs and model resolutions yield different results due to GCM specific parameterisation. Mutz et al (2018) conducted PMIP-style palaeoclimate experiments with the same GCM (ECHAM5) and resolution, which removes the GCM parameterisation related signal in the differences between simulated palaeoclimates. This experiment framework comprises climate simulations for the pre-industrial (PI, reference year 1850), Mid-Holocene (MH, ∼ 6 ka), Last Glacial Maximum (LGM, ∼ 21 ka) and Pliocene (PLIO, ∼ 3 Ma).…”
Section: Introductionmentioning
confidence: 99%